Tinjauan Pelaksanaan Sikda Optima di Pelayanan Pendaftaran Rawat Jalan di Puskesmas Kecamatan Kebon Jeruk - Khusnul Khatimah; Noor Yulia (Yayasan Literasi Sains Indonesia, 2026)
The purpose of this study is to identify the Standard Operating Procedures (SOP) for outpatient registration, the menu items involved, the features of the Sikda Optima system, and the obstacles encountered in outpatient registration at the Kebon Jeruk District Health Center. This research uses a descriptive quantitative method, which involves the collection, processing, and interpretation of data in numerical form. The results indicate that the SOP for outpatient registration has been implemented since January 3, 2023, and that the features of Sikda Optima are complete, meet user needs, and are easy to use; however, several obstacles remain, particularly system failures or errors during operation. The study concludes that the SOP is designed to facilitate administrative processes and ensure effective healthcare services, while the registration items play an important role in ensuring a smooth registration process. Despite the use of the Sikda Optima application, challenges still occur, such as system failures lasting more than 10 minutes that cause the website to become inaccessible, and the lack of integration with the P-Care system, requiring staff to perform double data entry. Therefore, it is recommended that a responsive technician be available to monitor system connectivity during service hours and that system features be improved to enhance efficiency and effectiveness, as the SOP ultimately helps improve service quality, reduce queues, and ensure more accurate patient data recording.